Black light-permeable halogen-free flame-retardant reinforced nylon as well as preparation method and application thereof

By using specially made light-transmissive toner and halogen-free flame retardant composites in nylon materials, combined with efficient extrusion technology, the environmental protection, light-transmissiveness and leakage resistance of halogen-free flame retardant nylon materials are solved. , achieving uniform light distribution and excellent flame retardant performance.

CN119286177APending Publication Date: 2025-01-10GUANGDONG GREAT MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411576502.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing halogen-free flame retardant nylon materials have problems such as poor environmental protection, poor light transmission, uneven light distribution and insufficient leakage resistance in electronic equipment. In particular, traditional halogen-free flame retardant will affect the light transmission performance of the material and Mechanical properties.

Method used

Using polymethyl methacrylate resin, glass fiber, halogen-free flame retardant composites, antioxidants and specially made light-transmitting toners, black light-transmitting can be prepared through efficient mixing and extrusion processes. Nylon, using silicone light diffusers and active copolymers to improve the dispersion and light distribution uniformity of toner.

Benefits of technology

It realizes a black halogen-free flame-retardant nylon material with good light transmission, with uniform light distribution and excellent leakage resistance, while maintaining good flame-retardant performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005121930130000051
    Figure BDA0005121930130000051
  • Figure BDA0005121930130000061
    Figure BDA0005121930130000061
Patent Text Reader

Abstract

The invention provides black light-transmitting halogen-free flame-retardant reinforced nylon as well as a preparation method and application thereof, the black light-transmitting halogen-free flame-retardant reinforced nylon comprises the following raw materials in percentage by weight: 30-50% of polymethyl methacrylate resin, 10-30% of glass fiber, 10-30% of a halogen-free flame retardant compound, 1-3% of an antioxidant and 1-3% of light-transmitting toner. The dispersion and the light transmission of the toner are improved by the organic silicon light diffusant and the active copolymer, and the nylon material prepared by combining the components has good light transmission, uniform light distribution and electric leakage resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nylon materials, and in particular to a black light-transmissive halogen-free flame-retardant reinforced nylon and a preparation method and application thereof. Background Art

[0002] With the continuous advancement of science and technology, the electronic equipment industry is booming. Electronic equipment plays an increasingly important role in people's lives and work. From smart phones and tablets to various household appliances and industrial control equipment, its application range is constantly expanding. In the design and manufacturing process of electronic equipment, the performance requirements for materials are also getting higher and higher.

[0003] As an engineering plastic, nylon has many excellent properties, which makes it widely used in the field of electronic equipment. First of all, nylon has good mechanical properties, including high strength, high toughness, and wear resistance. This enables nylon materials to withstand various external forces and wear that electronic equipment may be subjected to during use, ensuring the structural stability and service life of the equipment. Secondly, nylon has good heat resistance and chemical corrosion resistance, and can maintain stable performance under different environmental conditions. In addition, nylon also has good processing properties, and can be made into parts of various shapes and sizes through various processing methods such as injection molding and extrusion to meet the design requirements of electronic equipment.

[0004] In electronic equipment, flame retardant properties are crucial. Traditional flame retardant materials usually contain halogens, such as bromine and chlorine. Although halogen flame retardants have good flame retardant effects, they release toxic hydrogen halide gas during combustion, which causes serious harm to human health and the environment. With the continuous improvement of environmental awareness, halogen-free flame retardant materials have gradually become the development trend of the electronic equipment industry. Halogen-free flame retardant materials do not release toxic gases during combustion, which is more environmentally friendly and safe. At the same time, halogen-free flame retardant materials can also achieve flame retardant properties comparable to or even better than traditional halogen flame retardant materials by optimizing formulations and processes. In the prior art, the research and development of halogen-free flame retardant nylon materials mainly focuses on improving flame retardant properties, while less attention is paid to the light transmittance of the materials. Traditional halogen-free flame retardants usually affect the light transmittance of the materials, making it difficult for the materials to maintain the light transmittance while achieving good flame retardant properties. In electronic equipment applications, high anti-leakage performance and light transmittance requirements limit the application of halogen-free flame retardant nylon materials in some specific electronic equipment. Adding translucent color powder can make nylon material translucent, but factors such as the type, amount and dispersibility of the color powder will also affect the performance of the material. If the color powder is not selected properly or the amount is too much, it may reduce the flame retardancy, leakage resistance and mechanical properties of the material. In addition, the dispersibility of the color powder is also a key issue. If the color powder is not evenly dispersed in the nylon material, it may cause problems such as uneven color and inconsistent light transmittance of the material, affecting the appearance quality and performance stability of the material.

[0005] In view of the problems existing in the prior art, the present application aims to solve the problems of nylon being environmentally unfriendly, having poor light transmittance, uneven light distribution, and poor anti-leakage performance. Summary of the invention

[0006] Purpose of the invention:

[0007] The purpose of the present invention is to provide a preparation method and application of black light-transmitting halogen-free flame-retardant reinforced nylon, so as to solve the problems of nylon's environmental non-environmental properties, poor light transmittance, uneven light distribution and poor anti-leakage performance.

[0008] The technical solution of the present invention:

[0009] The invention discloses a black light-transmitting halogen-free flame-retardant reinforced nylon, which is characterized in that the raw materials of the black light-transmitting halogen-free flame-retardant reinforced nylon are 100% by weight and include the following components: 30-50% of polymethyl methacrylate resin, 10-30% of glass fiber, 10-30% of halogen-free flame retardant compound, 1-3% of antioxidant and 1-3% of light-transmitting color powder.

[0010] Furthermore, the weight average molecular weight of the polymethyl methacrylate resin is 8 to 12 kDa.

[0011] Furthermore, the raw materials for preparing the light-transmitting toner include: carbon black, organic silicon light diffuser, and active copolymer.

[0012] The preparation of the light-transmitting toner comprises the following steps:

[0013] S1: Add a certain amount of carbon black, silicone light diffuser and active copolymer into a high-speed mixer in proportion, with a rotation speed of 1000-2000 rpm and a mixing time of 15-30 minutes to pre-mix the three raw materials evenly;

[0014] S2: Transfer the premixed materials in step S1 to a three-roll mill with a roller spacing of 0.1 to 0.5 mm and a rotation speed of 80 to 150 rpm;

[0015] S3: putting the material ground in step S2 into a drying device at a drying temperature of 60 to 80° C. for 2 to 4 hours, and sieving the dried material to obtain a light-transmitting toner.

[0016] Furthermore, the mass ratio of the carbon black, the organosilicon light diffuser and the active copolymer is 1-2:2.5-3.5:3-4.

[0017] The preparation of the active copolymer comprises the following steps:

[0018] SS1: Add weighed oleic acid and diethylenetriamine into a reaction kettle equipped with a stirring device, a thermometer and a reflux condenser, stir evenly, replace the air with nitrogen, and carry out condensation reaction at 150-200°C for 8-16 hours to generate an imidazoline intermediate;

[0019] SS2: Take another reactor equipped with a stirring device, a thermometer and a reflux condenser, add acrylic acid, sodium 1,6-naphthalene disulfonate, ammonium persulfate and the imidazoline intermediate prepared in step SS1 into the reactor, add an appropriate amount of ethanol solution, stir and dissolve, increase the temperature to 60-80°C, and react for 6-10 hours;

[0020] SS3: After the reaction in step SS2 is completed, the reaction is cooled, precipitated, and filtered to obtain an active copolymer.

[0021] Furthermore, the mass ratio of oleic acid to diethylenetriamine in step SS1 is 2-2.5:1; the mass ratio of acrylic acid, sodium 1,6-naphthalene disulfonate, ammonium persulfate, and imidazoline intermediate in step SS2 is 40-60:4-6:1:5-10.

[0022] Furthermore, the halogen-free flame retardant compound is a mixture of magnesium hydroxide and aluminum hydroxide; the mass ratio of the magnesium hydroxide to the aluminum hydroxide is 1 to 3:1.

[0023] The present application also provides a method for preparing black, light-transmitting, halogen-free, flame-retardant, reinforced nylon, which is characterized by comprising the following steps: mixing polymethyl methacrylate resin, a halogen-free flame retardant compound, an antioxidant, and light-transmitting color powder, adding the mixture to the main feed port of a twin-screw extruder, melt-mixing the mixture, adding glass fiber to the side feed port of the twin-screw extruder, mixing, extruding, and granulating the mixture, and cooling the mixture to obtain the black, light-transmitting, halogen-free, flame-retardant, reinforced nylon.

[0024] Furthermore, the antioxidant is one or more of antioxidant 1098, antioxidant 1010, antioxidant 1216, and antioxidant 1330.

[0025] Furthermore, the black light-transmissive halogen-free flame-retardant reinforced nylon is used in electronic equipment and light source alarms.

[0026] The surface of the organosilicon light diffuser has active groups and low surface energy. When mixed with light-transmitting toner, these characteristics enable the light diffuser to be adsorbed on the surface of the toner particles. Due to the flexibility of organosilicon and the mobility of the molecular chain, the light diffuser forms a structure similar to a "lubricating layer" on the surface of the toner particles, reducing the friction between the toner particles, thereby preventing the particles from agglomerating and improving the dispersibility of the toner in the system. The refractive index of the organosilicon light diffuser is usually different from that of the light-transmitting toner and the surrounding medium. When light passes through a system containing a light diffuser, due to the difference in refractive index, the light will be refracted and scattered at the interface between the light diffuser and the surrounding medium. This scattering effect makes the propagation path of light in the system more complicated and increases the chance of light contact with the toner particles. This scattering effect makes the light no longer propagate in a straight line, but forms a more uniform light distribution in the system. If the toner particles absorb less light, more light can pass through the system, thereby improving light transmittance. Reactive copolymers have groups that have an affinity for the toner surface and can bind to the toner particles through chemical bonding or physical adsorption. This combination allows the copolymer to form a coating on the surface of the toner particles. The coating can change the surface properties of the toner particles and improve their compatibility with the surrounding medium. Reactive copolymers can affect light transmittance by adjusting the microstructure of the system. Reactive copolymers can promote the uniform dispersion of toner particles in the system and reduce local aggregation, so that the propagation of light in the system will be more uniform, reducing light scattering and absorption caused by particle aggregation, thereby improving light transmittance. Reactive copolymers can improve light distribution through synergistic effects with light diffusers. Copolymers may affect the distribution state of light diffusers in the system, making them more evenly dispersed, thereby enhancing the scattering effect and uniformity of light.

[0027] Beneficial effects:

[0028] The invention provides a black light-transmitting halogen-free flame-retardant reinforced nylon, which is environmentally friendly and has good light transmittance, uniform light distribution and anti-leakage performance. DETAILED DESCRIPTION

[0029] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0030] Unless otherwise specified, the chemical reagents used in the present invention are all commercially available analytically pure.

[0031] The organosilicon light diffuser was purchased from Zhejiang Guanqi Nanotechnology Co., Ltd.; the commercially available light-transmitting color powder was purchased from Wenzhou Meirno Chemical Co., Ltd., model B-59.

[0032] Preparation of active copolymer A:

[0033] SS1: Add 2 kg of oleic acid and 1 kg of diethylenetriamine into a reactor equipped with a stirring device, a thermometer and a reflux condenser, stir evenly, replace the air with nitrogen, and carry out condensation reaction at 180°C for 10 hours to generate an imidazoline intermediate;

[0034] SS2: Take another reactor equipped with a stirring device, a thermometer and a reflux condenser, add 4 kg of acrylic acid, 0.4 kg of sodium 1,6-naphthalene disulfonate, 0.1 kg of ammonium persulfate and 1 kg of the imidazoline intermediate prepared in step SS1 into the reactor, add an appropriate amount of ethanol solution, stir and dissolve, increase the temperature to 80°C, and react for 6 hours;

[0035] SS3: After the reaction is completed, cool, precipitate and filter to obtain an active copolymer.

[0036] Preparation of active copolymer B:

[0037] The difference between this preparation and the active copolymer A is that 4 kg of acrylic acid, 0.4 kg of 1,6-sodium naphthalene disulfonate, 0.1 kg of ammonium persulfate and 1 kg of the imidazoline intermediate prepared in step SS1 in step SS2 are replaced by 6 kg of acrylic acid, 0.4 kg of sodium 1,6-naphthalene disulfonate, 0.1 kg of ammonium persulfate and 0.8 kg of the imidazoline intermediate prepared in step SS1.

[0038] Preparation of active copolymer C:

[0039] The difference between this preparation and the active copolymer A is that 4 kg of acrylic acid, 0.4 kg of sodium 1,6-naphthalene disulfonate, 0.1 kg of ammonium persulfate and 1 kg of the imidazoline intermediate prepared in step SS1 in step SS2 are replaced by 2 kg of acrylic acid, 0.4 kg of sodium 1,6-naphthalene disulfonate, 0.1 kg of ammonium persulfate and 1 kg of the imidazoline intermediate prepared in step SS1.

[0040] Preparation of active copolymer D:

[0041] The difference between this preparation and the active copolymer A is that 4 kg of acrylic acid, 0.4 kg of 1,6-sodium naphthalene disulfonate, 0.1 kg of ammonium persulfate and 1 kg of the imidazoline intermediate prepared in step SS1 in step SS2 are replaced by 4 kg of acrylic acid, 0.4 kg of sodium 1,6-naphthalene disulfonate, 0.1 kg of ammonium persulfate and 2 kg of the imidazoline intermediate prepared in step SS1.

[0042] Preparation of light-transmitting toner A:

[0043] S1: 1 kg of carbon black, 2.5 kg of organosilicon light diffuser and 3 kg of active copolymer A were added into a high-speed mixer in proportion, the speed was 1500 rpm, the mixing time was 15 minutes, and the three raw materials were pre-mixed evenly;

[0044] S2: The premixed material in step S1 is transferred to a three-roll mill with a roller spacing of 0.5 mm and a rotation speed of 100 rpm;

[0045] S3: putting the material ground in step S2 into a drying device at a drying temperature of 65° C. for 2 hours, sieving the dried material and passing it through a 100-mesh sieve to obtain a light-transmitting toner.

[0046] Preparation of light-transmitting toner B:

[0047] The difference between this preparation and the light-transmitting toner A is that 3 kg of active copolymer A in step S1 is replaced by 3 kg of active copolymer B.

[0048] Preparation of light-transmitting toner C:

[0049] The difference between this preparation and the light-transmitting toner A is that 3 kg of active copolymer A in step S1 is replaced by 3 kg of active copolymer C.

[0050] Preparation of light-transmitting toner D:

[0051] The difference between this preparation and the light-transmitting toner A is that 3 kg of active copolymer A in step S1 is replaced by 3 kg of active copolymer D.

[0052] Preparation of light-transmitting toner E:

[0053] The difference between this preparation and the light-transmitting toner A is that the active copolymer A is not added.

[0054] Preparation of light-transmitting toner F:

[0055] The difference between this preparation and the light-transmitting toner A is that no silicone light diffusing agent is added.

[0056] Preparation of halogen-free flame retardant compounds:

[0057] 20 kg of magnesium hydroxide and 10 kg of aluminum hydroxide were weighed and put into a mixer, and mixed at 150 rpm for 15 minutes to obtain a halogen-free flame retardant compound.

[0058] Preparation of black light-transmitting halogen-free flame-retardant reinforced nylon:

[0059] The polymethyl methacrylate resin, the halogen-free flame retardant compound, the antioxidant and the light-transmitting color powder are mixed, added into the main feeding port of the twin-screw extruder, melt-mixed at 200° C. for 10 minutes, the glass fiber is added into the side feeding port of the twin-screw extruder, mixed and extruded into granules, the extrusion temperature is 230° C., the screw speed is 250 rpm, and after cooling, the black light-transmitting halogen-free flame-retardant reinforced nylon is obtained.

[0060] Examples 1 to 7

[0061] According to the above-mentioned preparation method of black light-transmitting halogen-free flame-retardant reinforced nylon, Table 1 is a list of ingredients of black light-transmitting halogen-free flame-retardant reinforced nylon of Examples 1 to 7 in percentage.

[0062] Table 1

[0063]

[0064]

[0065] Comparative Example 1:

[0066] Comparative Example 1 was prepared according to the above-mentioned method for preparing black light-transmissive halogen-free flame-retardant reinforced nylon. The difference between this preparation and Example 2 is: Preparation of halogen-free flame retardant compound: 20 kg of ammonium polyphosphate and 10 kg of melamine cyanurate were put into a mixer and mixed at 150 rpm for 15 minutes.

[0067] Comparative Example 2:

[0068] Comparative Example 2 was prepared according to the above-mentioned method for preparing black light-transmissive halogen-free flame-retardant reinforced nylon. The difference between this preparation and Example 2 is that the light-transmissive color powder is commercially available light-transmissive color powder.

[0069] The nylon materials prepared in Examples 1 to 7 and Comparative Examples 1 to 2 were prepared into strip samples of 2×5×10 mm, and light transmittance test and light distribution test were performed:

[0070] 1. Light transmittance test: According to the standard GB / T 2410-2008 “Determination of light transmittance and haze of transparent plastics”, the light transmittance of the nylon materials prepared in Examples 1 to 7 and Comparative Examples 1 to 2 was tested.

[0071] 2. Light distribution test: Divide the sample surface into 10 uniform grid areas, and use a photometer to measure the light intensity at each grid point one by one. By comparing the light intensity data of each grid point, calculate the standard deviation of the light intensity, and evaluate the uniformity of the light distribution. If the difference in light intensity at each grid point is small, it indicates that the light distribution is relatively uniform; otherwise, it is uneven.

[0072] 3. CTI value test: Prepare nylon material into a sample with a size of 15mm×15mm×3mm, start with a voltage of 300V, and control the droplet size to 20mm 3 It is best to drip droplets on the sample surface at intervals of 30s until 50 drops of electrolyte are dripped, and then increase or decrease the voltage value (in multiples of 25V) to repeat the test until two adjacent voltage values ​​are obtained (a smaller voltage has no leakage after 50 drops, and a larger voltage has leakage), and determine the smaller voltage value as the CTI value of the material, among which, Level I: CTI value>600V, Level II: 400V≤CTI value<600V, Level III: 250V≤CTI value<400V.

[0073] Table 2: Test results

[0074] Material Light transmittance / % Standard deviation of light intensity / % CTI value level Example 1 86 4.2 Level I Example 2 88 3.8 Level I Example 3 86 4.0 Level I Example 4 82 6.5 Level I Example 5 80 6.2 Level I Example 6 62 10.2 Level I Example 7 72 8.8 Level I Comparative Example 1 85 4.2 Level II Comparative Example 2 60 15.5 Level I

[0075] From the above data, it can be seen that the black light-transmitting halogen-free flame-retardant reinforced nylon of Examples 1 to 3 has good light transmittance, uniform light distribution, and anti-leakage performance, and the black light-transmitting halogen-free flame-retardant reinforced nylon prepared in Examples 1-3 is subjected to vertical burning (1.6mm) test using the UL94 standard, and all are V-0 grade, having good flame retardancy; from the comparison between Example 4 and Example 2, it can be seen that when preparing the light-transmitting color powder, the raw material ratio of the active copolymer is unreasonable, which will make the light transmittance and uniform light distribution of the prepared black light-transmitting halogen-free flame-retardant reinforced nylon worse; from the comparison between Example 5 and Example 2, it can be seen that when preparing the light-transmitting color powder, the raw material ratio of the active copolymer is unreasonable, which will make the light transmittance and uniform light distribution of the prepared black light-transmitting halogen-free flame-retardant reinforced nylon worse; From the comparison between Example 6 and Example 2, it can be seen that when preparing the light-transmitting color powder, if the active copolymer is not added, the light transmittance and uniform light distribution of the prepared black light-transmitting halogen-free flame-retardant reinforced nylon will be deteriorated; from the comparison between Example 7 and Example 2, it can be seen that when preparing the light-transmitting color powder, if the silicone light diffusing agent is not added, the light transmittance and uniform light distribution of the prepared black light-transmitting halogen-free flame-retardant reinforced nylon will be deteriorated; from the comparison between Comparative Example 1 and Example 2, it can be seen that when the halogen-free flame retardant compound is unreasonable, the anti-leakage performance of the prepared black light-transmitting halogen-free flame-retardant reinforced nylon will be deteriorated; from the comparison between Comparative Example 2 and Example 2, it can be seen that when commercially available light-transmitting color powder is used, the light transmittance and uniform light distribution of the prepared black light-transmitting halogen-free flame-retardant reinforced nylon will be deteriorated, and the expected effect cannot be achieved.

[0076] The present invention can also have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.

Claims

1. A black light-transmissive halogen-free flame-retardant reinforced nylon, characterized in that: The raw materials of the black light-transmissive halogen-free flame-retardant reinforced nylon are 100% by weight, and include the following components: 30-50% polymethyl methacrylate resin, 10-30% glass fiber, 10-30% halogen-free flame retardant compound, 1-3% antioxidant, and 1-3% light-transmissive color powder.

2. The black light-transmissive halogen-free flame-retardant reinforced nylon according to claim 1, characterized in that: The weight average molecular weight of the polymethyl methacrylate resin is 8 to 12 kDa.

3. The black light-transmissive halogen-free flame-retardant reinforced nylon according to claim 1, characterized in that: The raw materials for preparing the light-transmitting color powder include: carbon black, organic silicon light diffusing agent, and active copolymer.

4. The black light-transmissive halogen-free flame-retardant reinforced nylon according to claim 3, characterized in that: The preparation of the light-transmitting toner comprises the following steps: S1: Add a certain amount of carbon black, silicone light diffuser and active copolymer into a high-speed mixer in proportion, with a rotation speed of 1000-2000 rpm and a mixing time of 15-30 minutes to pre-mix the three raw materials evenly; S2: Transfer the premixed materials in step S1 to a three-roll mill with a roller spacing of 0.1 to 0.5 mm and a rotation speed of 80 to 150 rpm; S3: putting the material ground in step S2 into a drying device at a drying temperature of 60 to 80° C. for 2 to 4 hours, and sieving the dried material to obtain a light-transmitting toner.

5. The black light-transmissive halogen-free flame-retardant reinforced nylon according to claim 4, characterized in that: The mass ratio of the carbon black, the organosilicon light diffuser and the active copolymer is 1-2:2.5-3.5:3-4.

6. The black light-transmissive halogen-free flame-retardant reinforced nylon according to claim 3, characterized in that: The preparation of the active copolymer comprises the following steps: SS1: Add weighed oleic acid and diethylenetriamine into a reaction kettle equipped with a stirring device, a thermometer and a reflux condenser, stir evenly, replace the air with nitrogen, and carry out condensation reaction at 150-200°C for 8-16 hours to generate an imidazoline intermediate; SS2: Take another reactor equipped with a stirring device, a thermometer and a reflux condenser, add acrylic acid, sodium 1,6-naphthalene disulfonate, ammonium persulfate and the imidazoline intermediate prepared in step SS1 into the reactor, add an appropriate amount of ethanol solution, stir and dissolve, increase the temperature to 60-80°C, and react for 6-10 hours; SS3: After the reaction in step SS2 is completed, the reaction is cooled, precipitated, and filtered to obtain an active copolymer.

7. The black light-transmissive halogen-free flame-retardant reinforced nylon according to claim 6, characterized in that: The mass ratio of oleic acid to diethylenetriamine in step SS1 is 2-2.5:1; the mass ratio of acrylic acid, sodium 1,6-naphthalene disulfonate, ammonium persulfate and imidazoline intermediate in step SS2 is 40-60:4-6:1:5-10.

8. The black light-transmissive halogen-free flame-retardant reinforced nylon according to claim 6, characterized in that: The halogen-free flame retardant compound is a mixture of magnesium hydroxide and aluminum hydroxide; the mass ratio of the magnesium hydroxide to the aluminum hydroxide is 1 to 3:

1.

9. The method for preparing the black light-transmissive halogen-free flame-retardant reinforced nylon according to claims 1-8, characterized in that: The following steps are involved: The polymethyl methacrylate resin, the halogen-free flame retardant compound, the antioxidant and the light-transmitting color powder are mixed and added to the main feeding port of the twin-screw extruder for melt mixing. The glass fiber is added to the side feeding port of the twin-screw extruder for mixing, extruding and granulating. After cooling, the black light-transmitting halogen-free flame retardant reinforced nylon is obtained.

10. Use of the black light-transmissive halogen-free flame-retardant reinforced nylon according to any one of claims 1 to 8 in electronic equipment and light source alarms.